2010
DOI: 10.3892/ijmm_00000387
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of nucleocytoplasmic β-N-acetylglucosaminidase (O-GlcNAcase) activity in thyroid cancers

Abstract: Abstract. Single N-acetylglucosamine residues attached by O-linkage to serine or threonine (O-GlcNAc) are an abundant, dynamic and inducible post-translational modification of cytoplasmic and nuclear proteins. This study analyzes the activity of the enzyme involved in the removal of these sugar residues, i.e. ß-N-acetylglucosaminidase (O-GlcNAcase) as well as the level of O-GlcNAc in benign and malignant thyroid lesions. Our results demonstrate increased activity of the enzyme in thyroid cancers in comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Additionally, a previous study proposed OGA activity to be significantly higher and O-GlcNAcylation to be lower in tumor tissue compared with corresponding normal tissue (31). Similarly, a different study demonstrated increased activity of OGA A B activity and decreased O-GlcNAc levels in thyroid cancer compared with benign lesions (16). By contrast, the present study demonstrated that an increase in O-GlcNAcylation was advantageous for the malignancy of ATC cells; however, the two different findings were not mutually contradictory.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, a previous study proposed OGA activity to be significantly higher and O-GlcNAcylation to be lower in tumor tissue compared with corresponding normal tissue (31). Similarly, a different study demonstrated increased activity of OGA A B activity and decreased O-GlcNAc levels in thyroid cancer compared with benign lesions (16). By contrast, the present study demonstrated that an increase in O-GlcNAcylation was advantageous for the malignancy of ATC cells; however, the two different findings were not mutually contradictory.…”
Section: Discussionmentioning
confidence: 96%
“…Although it has been proposed that aberrant O-GlcNAc metabolism is associated with the malignant properties of a variety of thyroid cancer cell types, and previous studies have indicated that O-GlcNAcylation participates in the functional regulation of ATC cells by modulating Akt1 activity (16,17), the exact roles of O-GlcNAc in thyroid cancer pathogenesis and progression remain to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies concerning O-GlcNAcylation in thyroid lesions demonstrated increased activity of O-GlcNAcase in cancers in comparison to non-neoplastic cells (20). Thus, we expected that an increase in O-GlcNAcylation would be disadvantageous for anaplastic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced O -GlcNAcylation level corresponding to increased OGT and decreased OGA expression is commonly observed in various cancers including bone (41), bladder (42), breast (26, 4345), bile duct (46), colon (4749), leukemia (50), liver (51), lung (47), ovary (36), pancreas (30), and prostate (52, 53). Alteration of this glycosylation in thyroid cancer, however, occurs in the opposite way (54). Interestingly, no mutations in OGT and OGA genes have been reported in human cancers, suggesting that these enzymes are tightly conserved.…”
Section: Regulation Of O-glcnac Cycling Enzymes and O-glcnacylationmentioning
confidence: 99%